Bibliometric Analysis of Global Research on Cancer Photodynamic Therapy: Focus on Nano-Related Research - Cheng, Kunming; Guo, Qiang; Shen, Zefeng; Yang, Weiguang; Wang, Yulin; Sun, Zaijie; Wu, Haiyang (Frontiers in Pharmacology, 2022)
A growing body of research has illuminated that photodynamic therapy (PDT) serves as an important therapeutic strategy in oncology and has become a hot topic in recent years. Although numerous papers related to cancer PDT (CPDT) have been published, no bibliometric studies have been conducted to summarize the research landscape, and highlight the research trends and hotspots in this field. This study collected 5,804 records on CPDT published between 2000 and 2021 from Web of Science Core Collection. Bibliometric analysis and visualization were conducted using VOSviewer, CiteSpace, and one online platform. The annual publication and citation results revealed significant increasing trends over the past 22 years. China and the United States, contributing 56.24% of the total publications, were the main driving force in this field. Chinese Academy of Sciences was the most prolific institution. Photodiagnosis and Photodynamic Therapy and Photochemistry and Photobiology were the most productive and most co-cited journals, respectively. All keywords were categorized into four clusters including studies on nanomaterial technology, clinical applications, mechanism, and photosensitizers. “nanotech-based PDT” and “enhanced PDT” were current research hotspots. In addition to several nano-related topics such as “nanosphere,” “nanoparticle,” “nanomaterial,” “nanoplatform,” “nanomedicine” and “gold nanoparticle,” the following topics including “photothermal therapy,” “metal organic framework,” “checkpoint blockade,” “tumor microenvironment,” “prodrug” also deserve further attention in the near future.